2018
DOI: 10.1111/jdi.12794
|View full text |Cite
|
Sign up to set email alerts
|

Role of inflammatory biomarkers in diabetic peripheral neuropathy

Abstract: Inflammatory pathway from hyperglycemia to diabetic peripheral neuropathy is very important in diagnosis and management. Inflammatory cytokine can be used for prediction and progression of diabetic peripheral neuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 7 publications
1
59
1
Order By: Relevance
“…Human studies showed correlation between circulating cholesterol and lipids in development and progression of neuropathy [11][12][13] albeit the mechanisms remain unexplained. LXRα and β are ligand-activated nuclear receptors that bind metabolites of cholesterol 18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…Human studies showed correlation between circulating cholesterol and lipids in development and progression of neuropathy [11][12][13] albeit the mechanisms remain unexplained. LXRα and β are ligand-activated nuclear receptors that bind metabolites of cholesterol 18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…Human studies showed correlation between circulating cholesterol and lipids in development and progression of neuropathy 11-13 albeit the mechanisms remain unexplained. LXRα and β are ligand-activated nuclear receptors that bind metabolites of cholesterol 18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies have focused on glucose as a major culprit in the development of Obesity-associated neuropathies 4-6 , but recent body of evidence indicated that altered plasma lipid signaling in the peripheral nervous system (PNS) 7-10 is involved. Indeed, evidence on obese and diabetic patients, and murine model of Type II diabetes strongly suggest that circulating cholesterol and inflammation are linked to development and progression of neuropathy 11-13 . However, the mechanisms underlying how lipids affect cells of the PNS are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…DPN is thought to be caused by the cellular damage and inflammatory cascade induced by chronic hyperglycaemia and dyslipidaemia, which arise from insulin resistance. However, many people with established T2DM develop DPN despite adequate glucose control, and current evidence does not prove the effectiveness of intensive glycaemic control on DPN progression in T2DM .…”
Section: Discussionmentioning
confidence: 99%
“…35 The individually tailored exercise counselling approach might also enhance self-management skills and facilitate building exercise habits into lifestyle, as DPN is associated with a lower level of self-care in areas including exercise and diet management. 36 DPN is thought to be caused by the cellular damage and inflammatory cascade induced by chronic hyperglycaemia and dyslipidaemia, [37][38][39][40][41] which arise from insulin resistance. However, many people with established T2DM develop DPN despite adequate glucose control, 3 and current evidence does not prove the effectiveness of intensive glycaemic control on DPN progression in T2DM.…”
Section: Adverse Eventsmentioning
confidence: 99%